Development of a Household Solar Power Plant: System Using Solar Panels. Issue 1 (March 2020) - Suyanto, M; Rusianto, T; Subandi,
Abstract: The purpose of this study was to find a model system of power generation by using solar-cells for house. The research was a realization of concern in overcoming the electricity energy crisis. Solar panels, inverters, batteries, and solar charge controllers were used to support on this study. Polycrystalline solar panels with 4 × 50Wp power were chosen to generate energy. The output voltage ranges from 14.8 to 17.5 V DC (direct current) per panel with a capacity of 2 × 70 Ah. Battery capacity of 24 volts was connected in series with an inverter of 1000 watts. The result of the study showed the voltage output of the solar panels was at maximum average of 30.2 V. The distribution of batteries charging used a solar charger controller at a voltage of 24.5 volt DC. The measurement of voltage resulted at the inverter output from 24 volt DC to converse of 220 volt AC (alternating current) without load. Voltage conditions as outputs of solar panels reach maximum voltage during the day from 10:00 am to 1:00 pm Western Indonesia Time (WIB) and it begin down until 6:00 pm. The design greatly influenced the performance of solar power plants.